Transformation of Marketing Macro-Economic Environment of Tourism with Emphasis on Changes in Mobility During COVID-19 Pandemic - Černá, Jana; Lejsková, Pavla; Ližbetinová, Lenka; Matúšová, Jana Galera (My University, 2022)
General activity in the tourism market has been stagnating since the market paralysis caused by the COVID-19 global pandemic. The situation is difficult to predict due to political and legislative interventions, changes in the economic performance of the tourism sector, and massive changes in demand. The paper aims at depicting the current macro-economic trends that have an impact on the tourism sector, thus contributing to the formation of some basis of inputs into the discussion concerning a possible orientation of the sector and businesses and future creation of services and products in the European area. The objective is achieved using the model of PESTLE analysis based on a comparative analysis of the latest and the most recent factors of the macroeconomic marketing environment, the findings of a study on a change in mobility of the inhabitants of the Czech Republic, trends in the tourism sector before and after the COVID-19 pandemic. The presented findings provide a basis for discussion on the concept orientation and the creation of tourism services and products in the Czech Republic and Europe.
Transformace marketingového makroekonomického prostředí cestovního ruchu s důrazem na změny v mobilitě během pandemie COVID-19
Keywords: changes in mobility; COVID-19; macroeconomic environment; PESTLE; tourism; změny mobility; COVID-19; makroekonomické prostředí; PESTLE; cestovní ruch